2013
DOI: 10.1016/j.corsci.2012.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Cell response and corrosion behavior of electrodeposited diamond-like carbon films on nanostructured titanium

Abstract: Surface characteristics such as roughness and contact angle of flat and nanostructured titanium samples and diamond-like carbon films (DLC) electrodeposited on the nanostructured samples were evaluated. Also, the mechanical properties and the corrosion resistance of the samples were evaluated in phosphate buffered saline (PBS). Biocompatibility was assessed by analyzing an in vitro cell culture. Nanostructured samples presented better cell biocompatibility. DLC deposited onto nanostructured samples remained wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This is an amorphous material that has high inherent biocompatibility with bone, and has been applied using chemical vapour deposition onto heated cpTi abutment screws [140]. The application technique can be varied somewhat, and can include electrodeposition [142]. It should ideally include the deposition of an intermediate layer, such as amorphous silicon, to promote adhesion of DLC to the substrate [143].…”
Section: Surface Modification Of Titanium Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an amorphous material that has high inherent biocompatibility with bone, and has been applied using chemical vapour deposition onto heated cpTi abutment screws [140]. The application technique can be varied somewhat, and can include electrodeposition [142]. It should ideally include the deposition of an intermediate layer, such as amorphous silicon, to promote adhesion of DLC to the substrate [143].…”
Section: Surface Modification Of Titanium Alloysmentioning
confidence: 99%
“…It should ideally include the deposition of an intermediate layer, such as amorphous silicon, to promote adhesion of DLC to the substrate [143]. The aim has been to produce surfaces of improved corrosion resistance and enhanced biocompatibility, and there is experimental evidence that success with these aspects can be achieved in vitro [142,144,145]. However, despite this promise, this approach has not yet had any impact on clinical practice, and DLC-coated dental implants are not yet being used in patients.…”
Section: Surface Modification Of Titanium Alloysmentioning
confidence: 99%
“…In this respect, Jamesh et al [40] observed apatite deposition on the Ti after surface mechanical attrition treatment and immersion in simulated body fluids due to the formation of nano-structured grains in the near surface, higher surface roughness, surface wettability, and higher surface energy. Flamini et al [41] demonstrated that a polypyrrole film containing molybdate ions prepared by electrodeposition enhanced the corrosion resistance of NiTi in 0.15 M NaCl and Manhabosco et al [42] observed that a diamond-like carbon film prepared improved the corrosion resistance of Ti in the phosphate buffer saline solution. All in all, although TiO 2 , TiN x O y , bone-like apatite, polypyrrole, and DLC films prepared by various techniques have been shown to improve the corrosion resistance of Ti and its alloys, it is still necessary to optimize all the related properties including adhesion, biocompatibility, corrosion resistance, and covalent binding of protein molecules for biomedical applications.…”
Section: Introductionmentioning
confidence: 98%
“…The DLC films are also considered good candidates for biomedical applications due to their biocompatibility with human cells, which was widely studied. Further, because of their carbon and hydrogen composition, DLC films present optimal cell behavior and high rates of cell proliferation (3,4,(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%